On colombian reptiles and amphibians collected by dr. r. e. schultes (1947)
From Dr. Richard Evans Schultes, who has been engaged on botanical investigations in southeastern Colombia, the Museum of Comparative Zoölogy at Harvard College has recently received a fine herpetological collection. The collection consists of twenty-eight species, which, with the exception of one frog, were all taken at Leticia on the Amazon River in the Intendencia del Amazonas. We take this opportunity of thanking Dr. Schultes for his generous donation.